KOMUNIKASI LINGKUNGAN MASYARAKAT SUNGAI TABUK DALAM MENJAGA KEBERSIHAN SUNGAI - Achmad Bayu Chandrabuwono; Atika Atika (Universitas Lambung Mangkurat, 2019)
Environmental problems especially in the martapura riverbank not only solved with a effort to save the disaster only. Society awareness evenly requires seriousness by means of certain communication patterns. This study uses a qualitative approach with descriptive type. The study was conducted in Sungai Tabuk, Banjar. Based on the results of environmental communication research at the Martapura river community in Sungai Tabuk Sub-district to create a clean environment, judging by the elements of communication, the environmental communication has fulfilled all of these elements. Communication techniques used all communication techniques, namely informative, coercive, persuasive and human relationships.